Refurbishment works of shopping malls in Ipoh Perak / Ardina Umais Aminudin - Ardina Umais, Aminudin (2018)
Refurbishment works is an alternative ways to sustain the environment instead of demolished or abandoned it. Refurbishment works also can be done to improve facilities, rearrange the internal area or façade of the building. Shopping malls with ill-looking appearance can undergo refurbishment works and can enhance its technical performance to give a better environment to users and reached their satisfaction. Thus, the aim of this research is to identify which shopping malls in Ipoh that undergo refurbishment works. The objectives of this research are to identify shopping malls that experience refurbishment works, to determine the major changes of shopping malls that affected due to refurbishment works and to determine the level of users’ satisfaction towards refurbishment works of shopping malls. To achieve the objectives, data of this research were collected through observation and by distributing a questionnaire survey. The malls that were refurbished were identified and the major changes due to refurbishment works that affected due to refurbishment works are façade, general site, facilities and amenities, food court, ceiling finishes, floor finishes, railing, mechanical handling system and new tenants. The level of users’ satisfaction towards refurbishment works of shopping malls were determine. With this study, the exposure regarding the concept of refurbishment as a solution to gives a new life for old buildings can be practiced widely in Malaysia.